The Contribution of Rotating Savings and Credit Associations (ROSCAs) to the Economic Development of Rural Areas of Buhara Sub-County Kabale District. - Atukwase, Maurensia (Kabale University, 2024)
Globally, Rotating savings and credit associations are among the oldest and most prevalent savings institutions and they play an important role in savings mobilization in many developing economies. The purpose of this study was to find out the Contribution of Rotating Savings and Credit Associations (ROSCAs) to the Economic Development of Rural Areas of Buhara Sub-County Kabale District.